REFORMASI BIROKRASI KINERJA di BADAN KEPEGAWAIAN NEGARA KANTOR REGIONAL II SURABAYA - Cik Ida Kumalasari Amirudin; Oktarizka Reviandani (Jurnal Penelitian Administrasi Publik, 2021)
The bureaucracy is still marked by the low performance of human resources and the institutional apparatus; inadequate government institutional (organization) and management (management) systems; low work efficiency and effectiveness; low quality of public services; low welfare of civil servants; and the large number of laws and regulations that are no longer in accordance with the development of conditions and the demands of development, inefficient work mechanisms, the number of employees who are fat, the service process is slow, not modern or out of date, often misuses authority and the large number of KKN practices, is not responsive to the diversity of needs and local conditions. The research objective is to describe and analyze the implementation and process of bureaucratic reform in the performance of the State Civil Apparatus and its supporting and inhibiting factors. This type of descriptive research with a qualitative approach. The results showed that the Surabaya II State Civil Service Agency had difficulty in changing the mindset of employees. There is no specific arrangement of legislation in the Surabaya II Civil Service Agency. The National Personnel Agency has structured and strengthened the Organizational Structure and Work Procedures (SOTK) oriented towards Modern Organizations and Employees of a Professional and Dignified State Personnel Agency. The Surabaya City II Civil Service Agency carries out the preparation and refinement of the Operational Procedure Standards (SOP) in each work unit. In addition, the II State Civil Service Agency in Surabaya has difficulty developing Human Resources (HR), but has carried out supervision, accountability and improved quality of public services.